Penanganan Sludge Limbah Penyamakan Kulit Dengan Biometanogen - Triatmojo, Suharjono (Universitas Atma Jaya Yogyakarta, 2003)
This research is conducted to study the effect of anaerobic digestion on the reduction of BOD, COD, TSS, VFA, and Cr(VI) content and biogas production of industrial wastewater bearing chromium. Material used in this experiment are sludge of tannery waste and dairy cattle manure. Splitplot design was used in this research, as mainplot is level of sludge i.e. 0, 10, 20 and 30%, and the subplot is days of digestion i.e. 0, 10,20, and 30 days, respectively. The results of this research show that increasing level of chromium in the waste inhibit biological activity due to the toxicity of the chromium. Anaerobic digestion decreased the value of BOD, COD, TSS and Cr(VI) concentration, the value is 75.54%, 44.62%, 41.30% and 22.40%, respectively. Biogas production and VFA concentration decreased significanly after 20 days of digestion. The conclusion is biometanogen can be used to reduce the level of pollution of organic matter and Cr(VI). Anaerobic digestion can be used as alteranative of bioremediation of industrial wastewater bearing chromium.